1988
DOI: 10.1111/j.0954-6820.1988.tb19369.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Left Ventricular Diastolic Dysfunction in Long‐term Type I Diabetic Subjects

Abstract: Although non‐invasive studies in type I diabetic subjects indicate left ventricular (LV) diastolic dysfunction, the contribution of borderline or mild hypertension to such changes is obscure. Thus, digitized M‐mode echocardiograms were obtained in 32 (18 men) young (<50 years) normotensive controls and 32 (21 men) long‐term (≥12 years) type I diabetics with blood pressures ranging from normal to hypertensive. All diabetics were without clinical heart disease, none were previously treated for hypertension or us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Previous studies in diabetic adults have shown that aerobic capacity and left ventricular stroke volume during exercise are associated with diastolic dysfunction in adults. 152,154 Adults with asymptomatic type 1 diabetes have reduced exercise capacity and lower stroke volume at peak exercise compared with non-diabetic peers, limitations that are strongly associated with diastolic dysfunction 154,155 and reduced EDV during exercise. 152,154 Current evidence suggests that healthy adolescents with diabetes may also have lower aerobic capacity 156,157 and lower exercise stroke volume.…”
Section: Functional Changes In Cardiac and Peripheral Vascular Funcmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in diabetic adults have shown that aerobic capacity and left ventricular stroke volume during exercise are associated with diastolic dysfunction in adults. 152,154 Adults with asymptomatic type 1 diabetes have reduced exercise capacity and lower stroke volume at peak exercise compared with non-diabetic peers, limitations that are strongly associated with diastolic dysfunction 154,155 and reduced EDV during exercise. 152,154 Current evidence suggests that healthy adolescents with diabetes may also have lower aerobic capacity 156,157 and lower exercise stroke volume.…”
Section: Functional Changes In Cardiac and Peripheral Vascular Funcmentioning
confidence: 99%
“…152,154 Adults with asymptomatic type 1 diabetes have reduced exercise capacity and lower stroke volume at peak exercise compared with non-diabetic peers, limitations that are strongly associated with diastolic dysfunction 154,155 and reduced EDV during exercise. 152,154 Current evidence suggests that healthy adolescents with diabetes may also have lower aerobic capacity 156,157 and lower exercise stroke volume. 156 In a recent study, 52 adolescents with type 1 diabetic (mean duration of diabetes was 6 years) were assessed at rest and during submaximal exercise (at a fixed heart rate) by cardiac magnetic resonance imaging (MRI).…”
Section: Functional Changes In Cardiac and Peripheral Vascular Funcmentioning
confidence: 99%
“…Previous studies in diabetic adults have shown that aerobic capacity and left ventricular stroke volume during exercise are associated with diastolic dysfunction in adults (118,119). Adults with asymptomatic type 1 diabetes have reduced exercise capacity and lower stroke volume at peak exercise compared with non-diabetic peers, limitations that are strongly associated with diastolic dysfunction (119, Microvascular and macrovascular complications 120) and reduced EDV during exercise (118,119). Current evidence suggests that healthy adolescents with diabetes may also have lower aerobic capacity (121,122) and lower exercise stroke volume (121).…”
Section: Functional Changes In Cardiac and Peripheral Vascular Functionmentioning
confidence: 99%
“…Previous studies in diabetic adults showed that aerobic capacity and left ventricular stroke volume during exercise are associated with diastolic dysfunction in adults (5,6). Adults with asymptomatic type 1 diabetes have reduced exercise capacity and lower stroke volume at peak exercise compared with nondiabetic peers, limitations that are strongly associated with diastolic dysfunction (6,7) and reduced EDV during exercise (5,6). It remains unclear whether diabetic adolescents present similar alterations in left ventricular function.…”
mentioning
confidence: 96%